Neuroscience-Based Islamic Religious Education: Strengthening Students’ Spiritual Intelligence and Meaningful Learning - Najeeb Yahya; Helene Knudstad; Md. Sultan Mahmud (PT Barkah Ilmi Fiddunya, 2025)
Recent advances in neuroscience have provided valuable insights into how the brain processes learning, memory, emotion, and moral reasoning. Despite these developments, neuroscience has rarely been integrated into Islamic Religious Education (IRE). This study aims to develop a neuroscience-based instructional model that enhances students’ spiritual intelligence and promotes meaningful learning within Islamic educational settings. A research and development (R&D) approach was employed using the ADDIE model, including needs assessment, instructional design, expert validation, limited implementation, and evaluation. Data were collected through interviews, classroom observations, expert judgment, learning achievement tests, and students’ spiritual intelligence questionnaires. The findings indicate that learning activities designed according to neuroscientific principles such as emotional engagement, reflective learning, spaced repetition, storytelling, and experiential practice significantly improve students’ conceptual understanding, long-term memory retention, emotional regulation, and spiritual awareness. Furthermore, integrating Qur’anic reflection with neuroscience-informed pedagogical strategies creates a more engaging and student-centered learning environment. The novelty of this research lies in introducing an integrative neuroscience-based Islamic learning model that combines cognitive science, affective development, and Islamic spirituality to support holistic educational outcomes in the twenty-first century